Comparison of aboveground vegetation and soil seed bank composition at sites of different grazing intensity around a savanna-woodland watering point in West Africa - Sanou, Lassina; Zida, Didier; Savadogo, Patrice; Thiombiano, Adjima (Journal of plant research, 2018)
Grazing removes a plant’s aboveground vegetative and reproductive tissues and can modify the soil seed bank, potentially impacting the restoration of preferred species. Knowledge about aboveground vegetation and species composition of soil seed bank and the processes that contribute to vegetation recovery on and surrounding watering points subjected to grazing is lacking. Successful restoration strategies hinge on addressing these knowledge gaps. We assessed the effects of livestock grazing on aboveground vegetation and soil seed bank characteristics along a river bank and surrounding areas subject to different grazing intensities and draw implications for restoration. Plots (50 × 50 m) were established along five transects representing differing levels of grazing intensity. Soil samples were taken from three layers within each plot to determine soil properties and species composition of soil seed bank using the seedling emergence method. Heavy grazing resulted in the disappearance of perennial grasses, a reduction in species diversity and a decrease in soil nutrients with increased soil depth. Overall, the similarity between the extant aboveground vegetation and flora within the soil seed bank was low. The soil seed bank was dominated by herbaceous species and two woody species, suggesting that many woody species are not accumulating in the soil. With increasing soil depth, the seed density and richness declined. Canonical correspondence analyses (CCAs) showed that emerged seedlings from the soil seed bank were significantly influenced by soil carbon, organic matter, total nitrogen, total potassium and soil cation exchange capacity. This finding suggests that current grazing practices have a negative impact on the vegetation surrounding watering points; hence there is a need for improved grazing management strategies and vegetation restoration in these areas. The soil seed bank alone cannot restore degraded river banks; active transfer of propagules from adjacent undisturbed forest areas is essential.